Microhabitats de uma comunidade de pequenos mamíferos na restinga de Barra de Maricá, RJ - Carvalho, Beatriz Machado de (1989)
This study examines microhabitat configurations for a small mammal community in a "restinga" in Barra de Maricá, Rio de Janeiro's state. Habitat structure data were taken from the immediate vicinity of capture sites of the following species: Philander opossum, Akodon sp. do group cursor, Proechimys iheringi, Didelphis aurita, Sphiggurus insidiosus e Rattus rattus in two distinct mesohabitats: marshy grassland and "restinga" forest. Sixteen variables were measured for each of the 100 capture sites studied from January to October, 1986. Six variables, of particular significance for distinguishing the capture sites of that species from those of the three most frequently observed species each against the rest of the universe of samples, were identified. Discriminant analysis indicated the relative importance of each variable for characterizing species microhabitats. Proechimys iheringis microhabitat was found to be distinct from Akodon's and, in spite of the latter's wide distribution in the "restinga", it has a definitely stronger association with abundant herbaceous vegetation and few trees, as in the open spaces of marshy grassland.